Fineline Tattoo Design as a Form of Self Expression at Ingkeu Ink Tattoo Studio - Fauzi, Ivan; Tjokropramono, I Gede Yosef; Mustika, I Ketut (Program Studi Seni Murni ISI Bali, 2024)
The main objective of this research and art creation is to create and present the work